Effect of concentrates restriction on feed consumption, diet digestibility, and nitrogen utilization in captive Asian elephants (Elephas maximus). Issue 1 (16th December 2014) - Das, A.; Smith, M.L.; Saini, M.; Katole, Shrikant; Kullu, S.S.; Gupta, B.K.; Sharma, A.K.; Swarup, D.
<x xml:space="preserve">Abstract</x> In order to study the effect of concentrates restriction on feed consumption, diet digestibility, and utilization of nitrogen in captive Asian elephants (Elephas maximus), two feeding trials were conducted on three juveniles, four sub‐adults, and three adults. During trial I, the conventional zoo diets of juveniles, sub‐adults, and adult contained 22, 17, and 16% of concentrates on dry matter (DM) basis, respectively. During trial II, the amount of concentrate was reduced by 50%. A digestion trial of five days collection period was conducted during each period. The animals ate more roughages when concentrates were restricted. Intake of DM (g/kg BW0.75/day) was highest in sub‐adults, followed by juveniles and adults. Apparent digestibility of crude protein (CP), neutral detergent soluble (NDS), and supply of digestible energy (DE) was highest in juveniles, followed by sub‐adults and adults. Based upon the estimated metabolic fecal nitrogen (MFN) and calculated endogenous urinary nitrogen (EUN) and dermal losses, minimum dietary CP required to meet maintenance requirement was estimated to be 6.12, 6.05, and 5.97% in juveniles, sub‐adults, and adults, respectively. Restriction of concentrates resulted in decreased (P < 0.05) digestibility of DM and GE, but the diet still supplied adequate amounts of DE and CP to fulfill estimated requirements of energy and protein during the period of experimentation. Thus, the concentrates portion of the diets of captive Asian elephants should be fed in a restricted way so as to reduce the intake of excessive calories and the potential risk of obesity. Zoo Biol. 34:60–70, 2015. © 2014 Wiley Periodicals Inc.